2020
DOI: 10.1007/s42764-020-00027-6
|View full text |Cite
|
Sign up to set email alerts
|

Locked in a vicious cycle: the connection between genomic instability and a loss of protein homeostasis

Abstract: Cardiomyopathies, neuropathies, cancer and accelerated ageing are unequivocally distinct diseases, yet they also show overlapping pathological hallmarks, including a gradual loss of genomic integrity and proteotoxic stress. Recent lines of evidence suggest that this overlap could be the result of remarkably interconnected molecular cascades between nuclear genomic instability and a loss of protein homeostasis. In this review, we discuss these complex connections, as well as their possible impact on disease. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 247 publications
(268 reference statements)
0
8
0
Order By: Relevance
“…One of the factors underlying the AD-like phenotypes observed in GBM patients may be the genotoxic effects of radiotherapy and chemotherapy 22,23 . Indeed, studies have shown an association between DNA damage and a loss of protein homeostasis [24][25][26][27] . Remarkably, the proteins that aggregate after genotoxic stress overlap with proteins that aggregate in the background of neurodegenerative disease including AD 27 .…”
Section: Discussionmentioning
confidence: 99%
“…One of the factors underlying the AD-like phenotypes observed in GBM patients may be the genotoxic effects of radiotherapy and chemotherapy 22,23 . Indeed, studies have shown an association between DNA damage and a loss of protein homeostasis [24][25][26][27] . Remarkably, the proteins that aggregate after genotoxic stress overlap with proteins that aggregate in the background of neurodegenerative disease including AD 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Wild-type α-synuclein is unfolded and can be sequestered via many pathways, such as autophagy and CMA [ 54 ]. On the contrary, proteins that are encoded by mutant genes can misfold and begin a vicious cycle [ 55 ]. For example, overexpression of wild-type or mutant α-synuclein can compromise the degradation pathways ( Figure 1 ), causing abnormal buildup of α-synuclein that assembles, thus contributing to the formation of Lewy bodies in Parkinson disease brains [ 3 , 46 , 56 ].…”
Section: Role Of Autophagy In Parkinson Diseasementioning
confidence: 99%
“…As discussed, protein aggregation-induced DNA damage is rapidly emerging as a contributing factor in the aetiology of many age-related neurodegenerative disorders. Importantly, the relationship between protein homeostasis and genome stability is a two-way street-aggregation of specific proteins like amyloid-β, Tau, mutant Htt and α-synuclein can impact genome stability, but conversely, genome instability can also dramatically affect the proteome [133]. This is clearly exemplified by known genetic alterations in more than 30 human genes that are strongly associated with protein aggregation and disease [134].…”
Section: Dna Damage Leading To Loss Of Protein Quality Controlmentioning
confidence: 99%